Add: 12(x+4)+14(4x−2). Answer should be in mixed number form.

7 answers

To simplify the expression, we can distribute the coefficients:
12(x + 4) + 14(4x − 2)
= 12*x + 12*4 + 14*4x − 14*2
= 12x + 48 + 56x - 28
= 68x + 20

Converting the answer to mixed number form:
68x + 20
= 68x + 20/1
= (68x*1 + 20) / 1
= (68x + 20) / 1
= 68x + 20
Add: 12(x+4)+14(4x−2). Answer should be in mixed number form.
To simplify the expression, let's distribute the coefficients:
12(x + 4) + 14(4x − 2)
= 12x + 12 * 4 + 14 * 4x - 14 * 2 (Use the distributive property)
= 12x + 48 + 56x - 28 (Perform the multiplications)
= 68x + 48 - 28 (Combine like terms)
= 68x + 20

So, the simplified expression in mixed number form is 68x + 20.
thats wrong
Apologies for the confusion. Let's correct the mistake and simplify the expression once again:

12(x + 4) + 14(4x − 2)

= 12x + 48 + 56x − 28 (distributing the coefficients)
= 12x + 56x + 48 − 28 (combining like terms)
= 68x + 20 (combining like terms)

So, the correct simplified expression in mixed number form is 68x + 20.
Add: 1/2 (x+4)+1/4 (4x−2). Answer should be in mixed number form.
1/2 (x+4)+1/4 (4x−2)